Análise de livros didáticos de matemática: função exponencial - Masetti, Cristina (2016)
Our study aims to investigate how the exponential functions are covered in textbooks of Mathematics, offered to Brazilian schools by the National Textbook Program - PNLD, in 2015's high schools and how it is proposed the construction, systematization and consolidation of knowledge in these manuals. Our purpose is to analyze mathematical situations, concepts, propositions, procedures, language and arguments the textbook presents, accounting for different types of tasks the authors propose to the students for learning that knowledge. To this end, we sought the review the literature on studies of Mathematics textbook analysis, we read the curriculum guidelines of Mathematics for Secondary Education, and analyzed the books of the three collection of the 1st year of high school approved by PNLD 2015. We opted for the qualitative methodology and the technique of documentary analysis; furthermore, the data collection instruments were tables. Our work allowed us to conclude that the three analyzed textbooks offer teachers contextualized real life situations, of pure mathematics and other sciences, allowing interdisciplinarity, as well as to introduce the concept of exponential function within a context outside of mathematics seeking to promote student interest in the subject. All three books analyzed formally propose the power of review, not demonstrating, but justifying with solved exercises and an extensive list of manipulation tasks to be done. Therefore, regarding the emerging knowledge of exponential function we can say that the authors use language appropriate for the age group, offering various forms of representation in natural language, algebraic graphical and tabular, and argue using exercise resolution step by step. Predominates in three collections we analyze exponential function, handling exercises, few solving tasks of modeling problem that needs to get to the solution, and no statement of task, they prefer to justify themselves solving exercises that show all algebraic passages. Thus, from the analysis we can say that the textbooks investigated bring different tasks, allowing the teacher to provide differentiated learning situations, but are still few in number, one of them brings in a greater quantity of tasks to conjecture/argue compared to other books; in addition the author suggests to do these activities in pairs, which explains the fact that it brings fewer solved exercises, providing a high amount of problems to be solved and few manipulative exercises, the As compared to other works. So when the choice of which textbooks to be adopted by the school, the teacher to analyze it, needs to be aware of the characteristics of these books, in case of teach exponential functions, possible the necessity of having to offer higher amounts of certain learning situations to students, making additions and inclusions in the case of teaching demonstrations, with other curriculum materials, with the intent to report the curriculum requirements with regard to the teaching of exponential functions